Posterior reversible encephalopathy syndrome after lung transplantation: Risk factors and management. Issue 1 (7th December 2022) - Yavuz, Gökce; Heck, Suzette; Sienel, Wulf; Irlbeck, Michael; Kneidinger, Nikolaus; Michel, Sebastian; Forbrig, Robert; Walter, Julia; Zimmermann, Julia; Kovács, Julia; Glück, Olaf M.; Pan, Ming; et al.
Abstract: Introduction : Posterior reversible encephalopathy syndrome is a rare neurologic complication that can occur under immunosuppressive therapy with CNI after organ transplantation. Methods : We retrospectively reviewed medical records of 545 patients who underwent lung transplantation between 2012 and 2019. Within this group, we identified 30 patients with neurological symptoms typical of PRES and compared the characteristics of patients who were diagnosed with PRES ( n = 11) to those who were not ( n = 19). Results : The incidence of PRES after lung transplantation was 2%. Notably, 73% of the patients with PRES were female and the mean age was 39.2. Seizure (82% vs. 21%, p = .002) was the most common neurological presentation. The risk of developing PRES was significantly associated with age (OR = .92, p < .0001) and having cystic fibrosis (CF) (OP = 10.1, p < .0001). Creatinine level (1.9 vs. 1.1 mg/dl, p = .047) and tacrolimus trough level (19.4 vs. 16.5 ng/ml, p = .048) within 1 week prior to neurological symptoms were significantly higher in patients with PRES. Conclusion : Renal insufficiency and high tacrolimus levels are associated with PRES. A change of immunosuppressive drug should be done after confirmed PRES diagnosis or immediately in case of severe neurological dysfunction to improve neurological outcomes and minimize the risk of early allograft rejection.